2020
DOI: 10.1021/acs.macromol.0c00744
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Surface Segregation of Bottlebrush Polymer Additives in Thin Film Blends with Attractive Intermolecular Interactions

Abstract: The surface chemistry of polymer films and coatings is relevant to a wide range of applications, and recent work has shown that bottlebrush polymers can be used as additives to modify film interfaces and surfaces. In blends with linear polymers of a sufficient molecular weight, bottlebrush polymers will enrich interfaces driven, in part, by entropic effects. However, prior work has only studied a limited set of systems with either neutral or repulsive interactions between the bottlebrush and linear polymers. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 66 publications
1
26
0
Order By: Relevance
“…Spectral analysis is the simplest and most common and involves acquiring a high‐resolution mass spectrum for the surface under analysis. This can be used for a variety of purposes including identifying contaminants, 40,41 determining the relative abundances of elements or molecules, 38,39,42,43 studying the orientations of molecules on a surface, 44,45 or distinguishing between block and random copolymers 37 . For example, Liu et al analyzed poly(styrene– co –4‐vinyl phenol) (PS‐P4VP) random and block copolymers matched in size and composition 37 .…”
Section: Overview Of Tof‐simsmentioning
confidence: 99%
See 3 more Smart Citations
“…Spectral analysis is the simplest and most common and involves acquiring a high‐resolution mass spectrum for the surface under analysis. This can be used for a variety of purposes including identifying contaminants, 40,41 determining the relative abundances of elements or molecules, 38,39,42,43 studying the orientations of molecules on a surface, 44,45 or distinguishing between block and random copolymers 37 . For example, Liu et al analyzed poly(styrene– co –4‐vinyl phenol) (PS‐P4VP) random and block copolymers matched in size and composition 37 .…”
Section: Overview Of Tof‐simsmentioning
confidence: 99%
“…Several techniques have been developed to minimize or eliminate the matrix effect and achieve semi‐quantitative or quantitative analysis. Secondary ion intensities can be calibrated through analysis of well‐defined standards, and in many examples the ratios of secondary ion intensities depend linearly on the relative composition of the atomic or molecular species at the surface, 11,37,39,42,55–59 even when a strong matrix effect is present 55 . For the spectrum shown in Figure 3A, the authors showed that secondary ion intensities corresponding to either PS or P4VP varied linearly with the composition of the random copolymer, and therefore ToF‐SIMS could be used to quantify the copolymer compositions.…”
Section: Overview Of Tof‐simsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, there are additional entropic contributions favoring formation of ellipsoids for BBCP-3; the nematic alignment of the polymer chains at the wall favors the chain arrangement parallel to the confined wall, due to the entropic gain by maximizing the density of the side-chain ends at the free particle surface. In addition, the lower interfacial tension associated with perpendicular lamellae near the surface combined with the nematic effect contributes to the formation of ellipsoids. , To demonstrate the favored parallel chain alignment at the free surface, homopolymer bottlebrushes with different backbone chain lengths ( N BB = 32, 64, and 128) were simulated in a slit geometry (Figure (c)) as a control group. Parallel (⟨ R g 2 ⟩ ∥ ) and perpendicular (⟨ R g 2 ⟩ ⊥ ) components of the squared radius of gyration are shown in Figure (c), as a function of normalized distance from the free surface of the particle ( z / L ), ranging from 0 (surface) to 0.5 (center).…”
Section: Resultsmentioning
confidence: 99%